The Relationship Between Mother's Knowledge And The Completeness Of Basic Immunization For Children Aged 0-12 Months At Posyandu X, Bekasi Regency - Nuraeniah, Siti; Roza Indra Yeni; Maria Susila Sumartiningsih; Rima Berlian Putri (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Basic immunization is an important preventive strategy to protect infants from infectious diseases that can be prevented by vaccination. At Posyandu X, Bekasi Regency, basic immunization coverage has not yet reached the optimal target. One factor suspected to be the cause of this low coverage is the low level of knowledge of mothers regarding the importance of immunization, including its benefits, schedule, and potential side effects. Lack of information can impact low awareness and participation of parents in completing their children's immunizations. Objective: This study aims to determine the relationship between maternal knowledge levels and the completeness of basic immunizations in children aged 0–12 months. Method: This study used a quantitative method with a descriptive correlational approach and a cross-sectional design. The sample consisted of 80 mothers with infants aged 0–12 months, selected using a purposive sampling technique. The instruments used included a questionnaire to measure maternal knowledge levels and a checklist to assess the completeness of children's immunizations. Data analysis was performed using the Chi-Square test. Results: The results showed that most mothers had a low level of knowledge (48%). In addition, only 37.5% of infants received complete basic immunizations. The analysis results showed a significant relationship between maternal knowledge and the completeness of basic immunization (p < 0.05). Conclusion: Maternal knowledge is significantly related to the completeness of basic immunization in children aged 0–12 months. Therefore, it is recommended that Posyandu regularly provide education and counseling to improve maternal knowledge and basic immunization coverage in the community.